Exercise motivation during movement control order among UiTM Samarahan students / Awg Abdur Rahman Awg Masjarr - Awg Masjarr, Awg Abdur Rahman (2020)
Motivation was a key factor in determining whether a person could maintain a regular exercise routine. The purpose of this study was to identify exercise motivation among UiTM Samarahan students during movement control order. A total of 440 google form questionnaires were randomly distributed. The data collected were analysed by using the Statistical Package for the Social Science (SPSS) software version 22.0. My sampling technique used was stratified sampling to improve the accuracy and representativeness of the results by reducing sampling bias. Descriptive analysis was need to report the mean and standard deviation of general exercise motivation inventory chosen by respondent. Independent Sample T-Test was used for statistical analysis to investigate if there any significant difference of the exercise motivation that affect the desire to participate in exercise among students of UiTM Samarahan in terms of genders. There were 14 scales in EMI 2, which includes stress management, revitalisation, enjoyment, challenge, social recognition, affiliation, competition, health pressures, Ill-health avoidance, positive health, weight management, appearance, strength and endurance and nimbleness. The present study found 6 scales with significant mean differences that showed p<0.05. The scales were challenge, social recognition, affiliation, competition, positive health and nimbleness. Few past studies found that differences existed between male and female for enjoyment and appearance which not aligned with the finding of the current study. The differences in results might be caused by the different types of sampling, environment of pandemic covid-19 and as well as the limitations of the study.